Light- and Ca2+-modulated heterotrimeric GTPases in the eyespot apparatus of a flagellate green alga - Calenberg, Michael; Brohsonn, Uwe; Zedlacher, Marlies; Kreimer, Georg (The Plant Cell, 1998)
Little is known about phototactic signal transduction in flagellate green algae; therefore, eyespot apparatuses, which are the light-sensitive "organelles" involved in photoorientation of these algae, were isolated and analyzed for the presence of heterotrimeric guanine nucleotide binding proteins (G proteins) and their coupling to the retinal-based photoreceptor, Specific high-affinity S-35-GTP-gamma-S binding and GTPase activity, with sensitivity toward antibodies raised against vertebrate/invertebrate G(alpha) subunits and fluoroaluminates, were detected, In one-and two-dimensional immunoblot analyses, an antiserum directed against G(i alpha)-type subunits exhibited cross-reactivity at 42 kD, whereas a 43-kD protein cross-reacted with antisera directed against G(q alpha) subunits. Green light below 1 mu E m(-2) sec(-1) suppressed cholera toxin-dependent ADP ribosylation at these apparent molecular masses and modulated a significant proportion of the GTPase activity in a reversible manner. Antisera against Chlamydomonas rhodopsin and the G(alpha) subunits completely impaired light modulation, Both light sensitivity and dark recovery of the GTPase were affected by changes in free Ca2+. Dissociation of the putative G(alpha) subunits from the eyespot membranes was not observed when the membranes were illuminated. Our results emphasize the regulatory potential of G(alpha) subunits in rhodopsin-based signaling of flagellate green algae.